Effect of Temperature and Maceration Time on Characteristic of Ivory Coconut Husk (Cocos nucifera var. Eburnea) Extract as Tannin Source - Trisnadewi, Ni Nyoman Desi; Wrasiati, Luh Putu; Permana, IDG Mayun (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 7 No 2 (2020): Scientific Journal of Food Technology (September)DO - 10.24843/MITP.2020.v07.i02.p06, 2021)
Coconut husk from  ivory coconut can be utilized by taking the existing potential compounds . Tannin compounds in ivory coconut husk are obtained by extraction using maceration methods . The purpose of this study was to determine the effect of temperature and time of maceration and determine the treatment that produced the best ivory coconut husk extract .  Extraction of ivory coconut husk using ethanol with temperature and maceration time which consists of 70 ± 2 °C, 80 ±  2 °C, 90 ± 2 °C and maceration time 1 hour, 2 hours, 3 hours. Based on the results of the analysis of temperature variations and maceration time yield, tannin content, solubility, pH, and color intensity of  ivory coconut husk extract. The results of the effectiveness index test showed that the temperature of 80 ± 2 °C and within 2 hours was able to produce the best ivory coconut husk extract characteristics with yield characteristics of 18 .37 1 ± 0 .155%, tannin levels  13 .89  ±  1.09  g   TAE/100g, pH 3 .15, solubility 9 9.46  ±  0.24 %, brightness (L *) 19 .488 ± 3 .190, redness (a *) 10 .523 ± 0 .417, yellowish (b*) 18 .39, R f  value of 0.62 which is the R f  of catechin compounds. The results of the study concluded that the temperature and maceration time treatment affected the characteristics of ivory coconut  husk extract. Increasing the temperature and maceration time to its optimum conditions can increase yield, tannin content, pH, solubility, redness (a *), and yellowish (b *) and decrease brightness (L *).